BMI and adipose tissue: Effect of a diet lactoovovegetariana - Rengifo Mansilla, Saúl Jonatan (2019)
Objective: The purpose of this research was to determine the effect of the program “And you gave me food” inthe BMI and adipose tissue of students from a private Adventist university Lima Peru. Methods: The samplewas 50 students. The pre experimental study was cross-sectional design and explanatory scope. To determinethe nutritional diagnosis indicator Body Mass Index was used and for the diagnosis of adipose tissue criterionBray G. Results: was used According indicator BMI at baseline, 56% (28) presented normal state nutrition andmalnutrition rest. When the program 78% of students assessed presented normal nutritional status. Accordingadipose tissue at the start of the program, 72% (36) of the students were rated average. At the end of the program92% (46) students had a normal classification. The statistical test was utilized student-Samples T where p =<0.005, showing no significant difference, however if you could demonstrate the effectiveness of the programinto the database. Conclusions: It was concluded that the program has a positive effect on body mass index andfat.